2021
DOI: 10.1002/ijc.33767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver cancer incidence and survival by subtypes across seven high‐income countries

Abstract: International comparison of liver cancer survival has been hampered due to varying standards and degrees for morphological verification and differences in coding practices. This article aims to compare liver cancer survival across the International Cancer Benchmarking Partnership's (ICBP) jurisdictions whilst trying to ensure that the estimates are comparable through a range of sensitivity analyses. Liver cancer incidence data from 21 jurisdictions in 7 countries (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The augmented effect of novel systemic therapies might be reflected by the significantly improved 1-year survival rates in our study cohort, which is in line with rates previously reported in most other countries [38].…”
Section: Discussionsupporting
confidence: 92%
“…The augmented effect of novel systemic therapies might be reflected by the significantly improved 1-year survival rates in our study cohort, which is in line with rates previously reported in most other countries [38].…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, we examined jurisdiction-level (ecological) associations between the percentage of patients diagnosed through an emergency presentation and the corresponding, previously reported, 1-year net survival estimates for 2010–14. 1 , 18 For each cancer site, we used a linear regression model treating jurisdiction-level net survival as the outcome and adjusting for jurisdiction-level percentage of emergency presentations and definition type (broad or narrow) used. To maximise statistical power in these analyses, jurisdiction-specific estimates were used for 17 jurisdictions (New Brunswick, Nova Scotia, Prince Edward Island, Manitoba, and Saskatchewan were considered individually, and not as part of a jurisdictional cluster).…”
Section: Methodsmentioning
confidence: 99%
“…The study forms part of the International Cancer Benchmarking Partnership (ICBP), a global collaboration of clinicians, policy makers, researchers, and data experts in 21 jurisdictions in seven countries, seeking to explain cancer survival differences between high-income countries with comprehensive cancer registries, similar health system expenditure, and universal health care, to help improve cancer care and outcomes. 1 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Liver resection is the main method used for the treatment of liver cancer, and the potential advantages of laparoscopy, such as minimally invasive technique, fewer complications, and shorter intraoperative hospital stay, have been identified [ 1 , 2 ]. Although patients could get an early diagnosis combined with comprehensive treatment nowadays, due to the tumor’s malignant character, the prognosis of liver cancer remains unsatisfactory [ 3 , 4 ]. Factors such as age, tumor size and tumor number, pathologic TNM stage, and vascular invasion have been identified as factors influencing the prognosis of liver cancer patients [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%